Pengamatan Gejala Penyakit CVPD pada 12 Spesies Tanaman Jeruk - LEUNARDUS, VEDERIS; WIRAWAN, I GEDE PUTU; SUADA, I KETUT; YUNITI, I GUSTI AYU DIAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Diseases Symptoms Observation at 12 Species of Citrus Plants This study was conducted to observe symptoms that showed by citrus plants which already tested by PCR carry CVPDr DNA Fragment. CVPDr is resistance gene to prevent plant from CVPD diseases. Based on observations in the field showed that five from twelve species showed the symptoms even already carry the gene. Five of them are Citrus reticulata Selayer Buleleng, Citrus nobilis Buleleng, Citrus nobilis Pecatu, Citrus nobilis Tabanan, dan Citrus reticulata Keprok Gianyar. Mutation analysis and homology analysis should be done after this observation to know why this gene is not functional to prevent CVPD diseases.